Mitigating Low-Pressure Membrane Fouling by Controlling the Charge of Precipitated Floc Particles - McLeod, Gregg A. (Journal of Membrane and Separation Technology, 2014)
Fouling presents the most significant obstacle to optimal low-pressure membrane plant performance. The occurrence of fouling tends to decrease production rates (flux), increase chemical usage incurred during clean-in-place (CIP) process, increase energy costs, shorten membrane life and reduce recovery. Fouling may be of organic or inorganic nature, necessitating more frequent dual chemical cleaning procedures. Regardless of the nature of the foulants, particulate loading onto the membrane fiber surface has been identified as a common mechanism of deteriorating performance. Particulates and colloidal materials such as turbidity, natural organic material (NOM), algae and precipitated coagulant floc accumulate on the membrane surface and disrupt the laminar flow of water through the element. Particulates can either attach or adhere to the membrane surface through electrostatic attraction. One method of reducing this fouling mechanism is to employ controlled coagulation as a direct feed or coupled with a clarification step prior to membrane process. Coagulation can attract and retain naturally occurring particulates and colloidal materials via charge neutralization. Then, by controlling the charge of precipitated floc particulates to align with the surface charge of the membrane element, both types of fouling can be mitigated. This Paper summarizes two demonstrations featuring a pressure feed and a submerged vacuum ultrafiltration (UF) system.